Identity as a resource or a demand. - Karishma K Singh; Andrew J Elliot; Elizabeth D Handley; Jeremy P Jamieson (PLoS ONE)
Individuals embody various social identities that can impact how they interface with the social environment. Stigma theories suggest that members of low-status or marginalized groups possess devalued social identities, and therefore, experience more stress. While social identities can lead to increased stress, individuals' appraisals of their identities are not necessarily perceived as harmful/demanding. Rather, social identities can also be appraised as resources or sources of strength bringing opportunities and facilitating goal attainment. Using the biopsychosocial (BPS) model of challenge and threat as a conceptual foundation, this research developed a novel measure to assess individuals' appraisals of their social identities. In Study 1 (N = 575), confirmatory factor analysis (CFA) evaluated the theorized factor structure (i.e., resource and demand appraisals) and assessed the overall fit of the model. Structural equation modeling (SEM) tested for associations between the resource and demand latent factors. Individuals appraising their ethnic-racial identity as a resource exhibited improved self and intergroup outcomes, while those perceiving it as a demand reported worse self-based and intergroup outcomes, as well as more distress. Study 2 (N = 743 Black and White Americans), which was preregistered, examined group differences in appraisals of ethnic-racial identity. SEM revealed that Black participants were more likely than White participants to appraise their ethnic-racial identity as demanding, leading to worse social and intergroup outcomes. Even when Black participants perceived their ethnic-racial identity as a resource, they still reported higher levels of discrimination, intergroup anxiety, and behavioral avoidance compared to their White counterparts. Implications for theory development and application to the stress literature are discussed.